Predictors of radiological progression of rheumatoid arthritis while receiving conventional synthetic disease-modifying antirheumatic drugs - O. B. Iaremenko; G. M. Mykytenko (Сучасні медичні технології)
The aim of the work is to study the predictors of rheumatoid arthritis (RA) radiological progression while using conventional synthetic disease-modifying antirheumatic drugs (csDMARDs).